The story of the keris as an intercultural miscommunication issue. - Ahmad, Abd Mua'ti @ Zamri; Hassan, Hamisah (Vasile Goldis Western University, 2011)
During the United Malays National Organization (UMNO) General Assembly in 2005, its youth wing leader Hishammuddin Tun Hussein Onn was shown by the media waving a keris (a traditional Malay dagger) as a symbol to defend the Malay supremacy and to threaten those who opposed the Malay special rights. There were mixed reactions from the public to such a notorious act. While his party comrades commended such heroic action, the act has also drawn uproar from other races especially the Chinese. A year later, in the following assembly Hishamuddin defended his usage of the keris, which to him was meant "to motivate the Malays". However, the Chinese politicians declared themselves unconvinced by Hishammuddin's explanations. Even the youth chief of the Malaysian Chinese Association (MCA), an allied party to UMNO, affirmed that Hishamuddin’s act was inappropriate and insensitive to multiracial setup of the country. Nonetheless, another analyst stated that "A keris does not make people uncomfortable. It is the gesture and brandishing that makes people uncomfortable". The unsettling feelings by all parties may have occurred as a result of misinterpretation or miscommunication amongst the communicators from different cultural background.